GULAYAN SA PAARALAN AND ITS IMPLICATION TO LEARNERS’ NUTRITIONAL STATUS AND ACADEMIC PERFORMANCE: Received: 1st September 2021; Revised: 09th February 2022, 11th March 2022, 5th April 2022; Accepted: 06th April 2022 - Lacuarin, Nenette M; Dapilos, Leopoldo A; Alvara, Michelle T; Tamban, Victoria E; Tabuac, Erica C; Alforja, Nilda S (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This study aimed to determine the implications of the utilization of yield from Malaban Elementary School Gulayan sa Paaralan Project (GPP) through the School-based Feeding Program (SBFP) on the learners’ nutritional status and academic performance. A descriptive research design was employed in this study. The respondents of the study were the 123 severely wasted and 400 wasted learners from Kinder to Grade VI of Malaban Elementary School, School Year 2018-2019. Based on the results of the study after the GPP utilization through SBFP, the nutritional status of the learners in terms of BMI showed improvement from severely wasted to wasted, and from waste to normal, some were from severely wasted to normal, together with their height and weight. Likewise, an improvement was also observed in the academic performance of the learners. Consequently, the GPP utilization through SBFP has positive implications on the nutritional status as indicated in the BMI, height, weight and academic performance of the learners. Hence, the researcher recommended that GPP needs to continue for it helps the schools in achieving the goals of the government in promoting and maintaining health and wellness among Filipino learners, for malnutrition is one of the biggest problems encountered by our country that affects the academic performance of the learners.